(untitled) (Blockchain, Web3 & Digital Trust Journal p-ISSN 3117-597X and e-ISSN 3117-5988, 2025)
A blockchain stores state, not data. An NFT token URI points to an image; the image itself lives somewhere else. A DAO proposal is a hash on-chain; the proposal text is hosted on a server. A DeFi protocol’s frontend is a React bundle on Vercel – one takedown notice away from disappearing. Web3 applications need decentralised storage and computing infrastructure that matches the decentralisation of the blockchain layer, yet most rely on centralised cloud services for everything except the smart contracts. We present the Decentralised Infrastructure Assessment Framework (DIAF), evaluating six storage platforms – IPFS, Filecoin, Arweave, Ceramic Network, EthStorage, and Swarm – and four decentralised computing platforms – Akash Network, Golem, Fluence, and Internet Computer – on real Web3 workloads including NFT metadata hosting, frontend deployment, off-chain data indexing, and decentralised ML inference. Our Infrastructure Quality Score (IQFS) measures data availability, retrieval latency, cost efficiency, censorship resistance, and developer experience. Arweave achieves the highest storage IQFS (0.896) through permanent one-time-payment storage. Akash achieves the highest compute IQFS (0.872) through Kubernetes-compatible decentralised deployment.